Rıza Tevfik ve Mufassal Kamus-u felsefesi - Onay, Şerif (My University, 2003)
1839'dan sonra Osmanlı Devleti'nin Avrupa devletleri ile kültürel ilişkiler artmıştır. Batılı tarzda açılan yeni okullara Felsefe dersleri konulmuş ve Batı felsefesinden Türkçe'ye felsefî eserler ve ders kitapları tercüme edilmeye başlanmıştır. Bu süreç modern felsefe terimlerinin Türkçe'ye girmesine neden olmuştur. Fakat Türkçe'de bu terimleri ifade edecek kelimeler olmadığı için felsefe terimleri problemi ortaya çıkmıştır. Bu problemi çözmek amacıyla sözlükler hazırlanmıştır. Mufassal Kamus-u Felsefe de bu sözlüklerden biridir ve şimdiye kadar incelenmemiştir. Bu çalışmamızda Mufassal Kamus-u Felsefe'nin, felsefe terim çalışmaları arasındaki yerini ve İslam felsefesi, kelam ve tasavvufla ilgili bazı maddeleri ele aldık. Birinci bölümde Mufassal Kamus-u Felsefe ve II. Meşrutiyet dönemi felsefe terimi çalışmaları hakkında verdik. II., III. ve IV. bölümlerde agnostisizm, neden, nedensellik, zühd ve imsak maddelerini tetkik ettik. Rıza Tevfik, Mufassal Kamus-u Felsefe'de modern batı felsefesinde yeni anlamlar kazanan felsefe terimlerini yazarken, terimlerin hem batı hem de doğu kültürlerindeki anlamlarına yer vermiş ve uzlaştırmaya çalışmıştır. ÖZGEÇMİŞ 1977 yılında Burdur'da doğdum. İlk ve orta öğrenimimi Burdur'da tamamladım. 1995-2000 yılları arasında Marmara Üniversitesi İlahiyat Fakültesi'nde lisans eğitimimi bitirdim. 2000 yılında Marmara Üniversitesi Sosyal Bilimler Enstitüsü'nde yüksek lisans eğitimine başladım. Rıza Tevfik ve Mufassal Kamus-u Felsefe isimli bir tez çalışması hazırladım. BİOGRAPHY I was born in Burdur in 1977. I finished my primary and secondary school in Burdur in 1995. I graduated from Denizli İmam-Hatip Lise. Between 1995-2000 I completed my university education in Marmara University The Faculty of Theology. In 2000, I started my master education in Marmara University Institute of Social Sciences. I completed the study of thesis Rıza Tevfik and Mufassal Kamus-u Felsefe. Name and Surname: Şerife Onay Field: Theology Programme: Philosophy and Religion Studies Supervisor: Doç. Dr. İsmail Kara Degree Awarded and Date: Master - July 2003 Mufassal Kamus-u Felsefe, Philosophy Dictionary

THE ANALYSIS OF SOME POINTS RELATED TO ISLAM PHILOSOPHY, SPEECH AND SUFISM IN MUFASSAL KAMUS-U PHILOSOPHY After 1839 the culturel relationships developed between European countries and Ottoman Empire. Philosophy lessons were added to the curriculum of schools which were opened new and had programs in western style. With that, works of philosophy and lessons books. Started to be translated from western philosophy to Turkish. And this period caused modern philosophy terms to take place in Turkish. However, as there weren't enough words to express these terms in Turkish, the problem of philosophy terms came out. Dictionaries were prepared to overcame this problem. Mufassal Kamus-u Felsefe is one of these dictionaries as well. And it hasn't been examined so far. In our that work, we have studied the place of Mufassal Kamus-u Felsefe among philosophy term studies and some points related to Islam philosophy terms during II. Constitution. In II, III. and IV. parts we analysed agnostisizm, causality and ascetisme. Rıza Tevfik tries to give the meanings of terms both in West and East cultures and comes to an agreement between them while writing the philosophy terms and gaining new meaning in modern West philosophy in the book Mufassal Kamus-u Felsefe
Keywords: Felsefe, İslam